Innovation of fish feed based on local raw materials for fish farmers in Tambong Village, Banyuwangi Regency - Liliyanti, Mita Ayu; Hanafi, Agung Fauzi; Wardhana, Prabuditya Bhisma Wisnu (Community Empowerment, 2025)
Banyuwangi Regency is a potential area for developing freshwater fish farming businesses in Indonesia. One of the fish farming groups is Santri Fish Farm, located in Tambong Village, Kabat District. This group cultivates tilapia for consumption and koi as ornamental fish. Feed is a crucial factor supporting successful cultivation, but high feed costs, reaching 30–70% of the total production cost, are a major obstacle in this endeavor. Therefore, this activity aims to enhance the self-reliance of fish farmers in utilizing local raw materials as alternative feed, such as fish meal, snail meal, and water hyacinth. The activities began with the preparation of tools and feed raw materials, training on formulation development, practical feed production, and evaluation. The response to the produced feed showed excellent results. Meanwhile, evaluation results indicated a 50% increase in participants' understanding and skills in formulating local-based feed.